Fluorescent Immunoassays for Detection and Quantification of Cardiac Troponin I: A Short Review - Radha, Remya (2021)
Cardiovascular diseases are considered one of the major causes of human death globally. Myocardial infarction (MI), characterized by a diminished flow of blood to the heart, presents the highest rate of morbidity and mortality among all other cardiovascular diseases. These fatal effects have triggered the need for early diagnosis of appropriate biomarkers so that countermeasures can be taken. Cardiac troponin, the central key element of muscle regulation and contraction, is the most specific biomarker for cardiac injury and is considered the “gold standard”. Due to its high specificity, the measurement of cardiac troponin levels has become the predominant indicator of MI. Various forms of diagnostic methods have been developed so far, including chemiluminescence, fluorescence immunoassay, enzyme-linked immunosorbent assay, surface plasmon resonance, electrical detection, and colorimetric protein assays. However, fluorescence-based immunoassays are considered fast, accurate and most sensitive of all in the determination of cardiac troponins post-MI. This review represents the strategies, methods and levels of detection involved in the reported fluorescence-based immunoassays for the detection of cardiac troponin I.